Proposal educational software for diagnosis of superficial micoses based on DHP (Revista Electrónica REDINE, 2018)
The purpose of the present research was the development of educational software, based on the Development of Thought Skills (DHP), to facilitate the study of Surface Mycosis, as part of the subject of Medical Microbiology II, addressed to students Of the sixth semester of Medicine of the Central University Lisandro Alvarado, of Barquisimeto, State Lara; Under the Special Project modality, completing three phases: Phase I diagnosis, in which the study of the need to design educational software for the teaching of Mycology as part of the Medical Microbiology II assignment content, with the use of a questionnaire Of opinion to a sample of the students of the sixth semester of Medicine; Phase II, corresponded to the design of the instructional material; Phase III, validation of the content of the educational software by experts in the subject, a Computer Engineering, a TSU in systems that advised the technical details of the instructional material and as subject of study: the students, those who provided the information of the Need to create educational software, through the implementation of a survey. The results obtained in the survey were analyzed with the SPSS statistical program, applying a frequency analysis, tabulating the data and representing with sector graphs, emphasizing in the opinion of the respondents to be in agreement mostly with the realization of an instructional material Updated using the new technologies complemented with the Development of Thought Skills. This instructional material was created on the basis of Web pages, designed in an interactive and user-friendly way, developing content using images for meaningful learning. The elaboration of the same is based on the use of the program. Macro macro sleep tissues, professional editor used for web pages.
Keywords: mycology; developing thinking skills; educational software